PENGEMBANGAN BRAND IMAGE MADRASAH BERBASIS ICT DI MTs NEGERI 3 BANJARNEGARA - Narwati Narwati (QALAM: JURNAL PENDIDIKAN ISLAM, 2020)
This study aims to determine the implementation, obstacles encountered and the community's response to the development of ICT-Based Madrasah Brand Image in Madrasah Tsanawiyah Negeri 3 Banjarnegara. The approach used in this research is qualitative with the type of research being descriptive analysis. Data collection techniques used by interviews, observation, and documentation. From the results of the study showed that the form of brand development of ICT-based Madrasah in the Madrasah Tsanawiyah Negeri 3 Banjarnegara through the Full Day School (FDS) program. This program is a learning innovation from the Banjarnegara 3 Madrasah Tsanawiyah Negeri 3 in order to improve quality and meet the needs of the people in the area today. Conclusion: indications of its implementation have not been effective. The solution from the madrasa to monitor and analyze the environment optimally.